Clinical Results after Combined Distal Femoral Osteotomy in Patients with Patellar Maltracking and Recurrent Dislocations - Frings, Jannik; Krause, Matthias; Akoto, Ralph; Frosch, Karl-Heinz (The Journal of Knee Surgery, 2019)
The purpose of this study is to analyze the clinical results after treatment of patellofemoral instability and maltracking caused by torsional or axial deformities of the lower extremity by combined distal femoral osteotomies (DFOs). We analyzed 31 DFOs (25 patients) with patellar maltracking and instability, treated in our clinic. Torsional angles and the leg axis in the frontal plane were measured preoperatively. Standardized scoring systems were determined pre- and postoperatively including a clinical examination. Nineteen cases of torsional and 12 cases of axis deformities were evaluated 27 (12–64) months postoperatively. Among those with torsional deformity, mean femoral torsion was –39.0 ± 8.8 degrees, tibial tuberosity to trochlear groove (TT-TG) 20.3 ± 4.5 mm. We performed 19 torsional (+11.4 ± 2.4 degrees) DFOs with medial patellofemoral ligament (MPFL) augmentation (n = 19), tibial tuberosity transfer (n = 14, 10.9 ± 6.0 mm), varus (n = 4, 3.3 ± 1.0 degrees), or valgus (n = 1, 7.0 degrees) correction. Among valgus deformities, the leg axis was 6.7 ± 2.3 degrees valgus and TT-TG 19.3 ± 5.0 mm. We performed 12 medially closing-wedge DFOs (7.6 ± 2.8 degrees) with MPFL augmentation (n = 12) and tibial tubercle transfer (n = 9, 11.4 ± 7.3 mm). Visual analogue pain scale improved from 6.2 to 1.5 (p = 0.000), Kujala score from 45.0 to 81.5 (p = 0.000), Lysholm score from 40.3 to 83.9 (p = 0.000), and Tegner score from 2.1 to 3.9 (p = 0.000). Preoperative cartilage damage significantly influences the postoperative functional outcome (Lysholm score) (p = 0.026) as well as the improvement in terms of the Kujala score (p = 0.045) in the overall collective. No redislocation was observed. Patellofemoral maltracking and instability in torsional and axis deformities can successfully be treated by combined DFOs with excellent clinical results. The coexistence of risk factors for patellar instability requires a combination of additional procedures to complement the osteotomy. Preoperative cartilage lesions significantly influence the clinical outcome.
Keywords: patella; torsional deformity; osteotomy; maltracking; instability